Wa?dat Al-Wujûd dalam Alquran - Nasution, ismail fahmi arrauf nasution (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2016)
Wa?dat al-wujûd is a doctrine that believes in the ultimate form of God. While the universe is believed as a shadow that totally depends on the Creator (?aqq Ta‘âlâ). Wa?dat al-wujûd is one of the most inciting topics debated by Muslim scholars in the middle time of Islam. The opponents of wa?dat al-wujûd has used to accuse it as heresy. They consider wa?dat al-wujûd as theologically rooted from Zoroastrianism, Hinduism, Platonism and Neoplatonism. The opponents of wa?dat al-wujûd generally come from “literal-minded” theologians. They tend to understand the Qur’an and ?adîth in its outward meaning. Whereas the inner meaning has abundantly been contained in the Qur’an. This paper is an effort to analyze some verses of the Qur’an by using ta’wîl (esoteric analysis) and to some extent is a reflection on Syamsuddin al-Sumatrani’s teaching. In the end, this paper argues that although literally term of wa?dat al-wujûd does not exist in the Qur’an, however, the analysis shows that the teaching of wa?dat al-wujûd is definitely rooted in the Qur'an.